2013
DOI: 10.3390/d5030641
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a Culturable Microbial Population from the Gastrointestinal Tract of the Wood-Eating Loricariid Catfish Panaque nigrolineatus

Abstract: Fish play a critical role in nutrient cycling and organic matter flow in aquatic environments. However, little is known about the microbial diversity within the gastrointestinal tracts that may be essential in these degradation activities. Panaque nigrolineatus is a loricariid catfish found in the Neotropics that have a rare dietary strategy of consuming large amounts of woody material in its natural environment. As a consequence, the gastrointestinal (GI) tract of P. nigrolineatus is continually exposed to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…Our finding that P. nigrolineatus fed a wood-diet or a mixed-diet has different fungal communities is consistent with previous and current research showing similar variations for the bacterial communities in different regions of the GI tract [30, McDonald, Watts and Schreier, manuscript in preparation]. Of particular interest is the hindgut, which contains cellulolytic bacteria [29] , [30] , [31] as well as sequences similar to C. macrocephala , which has been associated with waterlogged wood [63] , [64] ; any relationship between these bacteria and fungi and their role in the fish GI tract remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that P. nigrolineatus fed a wood-diet or a mixed-diet has different fungal communities is consistent with previous and current research showing similar variations for the bacterial communities in different regions of the GI tract [30, McDonald, Watts and Schreier, manuscript in preparation]. Of particular interest is the hindgut, which contains cellulolytic bacteria [29] , [30] , [31] as well as sequences similar to C. macrocephala , which has been associated with waterlogged wood [63] , [64] ; any relationship between these bacteria and fungi and their role in the fish GI tract remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…Using 16S rRNA and culture-based analyses, the enteric bacterial community of P. nigrolineatus appears distinct and specialised in each region of the GI tract. The dominant bacteria have 16S rRNA gene sequences similar to Proteobacteria, Firmicutes, Bacteriodetes and Actinobacteria [30] , [31] , [32] . The midgut contains phylotypes with high sequence similarity to cellulose degrading bacteria Clostridium, Cellulomonas, Bacteroides, Eubacterium and Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al, showed that gut bacterial community of grass carp is dominated by cellulolytic Aeromonas, followed by Enterobacter, Enterococcus, Citrobacter, Bacillus, Raoultella, Klebsiella, Hydrotalea, Pseudomonas, Brevibacillus and that an increase in intake of plant-fibre increases the diversity of cellulolytic bacteria [36]. Cellulose degrading bacteria Clostridium, Aeromonas, Cellulomonas and Bacteroides along with other nitrogen fixing species are reported to provide assimilable carbon in the wood eating fish Panaque nigrolineatus [38,39]. Clostridia also dominate the gut microbial flora in different marine herbivorous fish species [40].…”
Section: Functional Potential Of Fish Gut Microbiomementioning
confidence: 99%
“…While they are less studied, bacteria are also part of the decaying-wood microbial diversity [ 9 ] and are expected to contribute to wood decay. Indeed, tree species and wood decay class have been shown to significantly shape the structure of wood-inhabiting bacterial communities [ 10 ] and numerous bacteria present the capability of decomposing wood carbohydrates such as cellulose [ 11 12 ] and hemicelluloses [ 13 14 ]. Moreover, a few bacteria have also been described as being involved in lignin degradation [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%